L’affaire de la Religieuse de Rivette (1965-1967) - Sabine Rousseau (Cahiers d'Études du Religieux- Recherches Interdisciplinaires)
Suzanne Simonin, la religieuse de Diderot, a film byJacques Rivette, a director connected with LaNouvelle Vague and Les cahiers du cinéma, was censored in 1966 under de Gaulle's presidency. What role did the CatholicChurch play in this decision? Among Christians, there were two different attitudes. Father Jean Pihan and Pierre Goursat from the Office catholique du cinéma, de la radio et de la télévision, rallied the nuns from the Union des supérieures majeures against the film. According to them, morality had to be saved. On the contrary, other Christians, such as Marc Oraison and Françoise Vandermeersch, thought that censorship was useless and that films must be appreciated for their aesthetic qualities.